In-situ dispersed lithium ion battery positive electrode slurry and preparation method thereof
Through the in -situ -scattered preparation method, the highly decentralized lithium -ion battery is positive pulp, which solves the problem of poor decentralization and reunion in the existing technology, and significantly improves the electrochemical performance and low temperature discharge capacity of the battery.
Patent Information
- Application Number
- CN202411423930.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, the lithium-ion battery positive electrode slurry has problems such as severe particle agglomeration, poor dispersion, high solid content, large viscosity and easy settlement, resulting in poor electrochemical performance of the battery.
Adopt the in situ decentralized preparation method, and use the in situ dispersal raw material A1 and A2 to replace the in -situ -in -situ -in -situ -in -situ compound dispersion in the rubber fluid. , Form a highly decentralized lithium ion battery positive slurry.
The high decentralization and stability of the slurry is achieved, the granular reunion is suppressed, the consistency of the electrode is improved, the internal resistance of the battery is reduced, and the battery's multiplier performance and cycle performance are improved, especially the discharge capacity in low temperature environments.
Smart Images

Figure CN119381407A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, in particular to an in-situ dispersed lithium ion battery positive electrode slurry and a preparation method thereof. Background Art
[0002] As one of the most stable energy storage devices, lithium-ion batteries (LIBs) are widely used in hybrid electric vehicles, electric vehicles, mobile phones, computers and other aspects of life due to their low price, environmental friendliness, high capacity and good thermal stability. As one of the most important components of lithium-ion batteries, the cathode materials of lithium-ion batteries are currently widely used in the commercial market, including LFP, LCO, LMO, ternary materials such as lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide. As energy equipment puts forward the demand for higher energy density and power density of batteries, the grain size of cathode materials has gradually developed from micron to submicron and nanometer levels to shorten the migration distance of lithium ion insertion and extraction, increase the lithium ion migration rate, increase the battery active capacity, and improve the overall performance of the battery.
[0003] However, cathode materials with small particle sizes have large specific surface areas, and particles with high specific surface areas and high surface energy are more difficult to prepare slurries. Due to the van der Waals effect and electrostatic repulsion between particles in the slurry, it is easy for particles to agglomerate in the slurry, making it more difficult to disperse during the slurry preparation process.
[0004] Patent CN111162262A discloses a method for preparing a positive electrode slurry for a high-rate lithium-ion battery. It proposes a method of mixing a graphene dispersion with a viscose solution in an all-round ball mill to ensure that the graphene network is connected to the current collector and improve the electronic conductivity of the positive electrode; and uses carbon tube conductive slurry and graphene dispersion to improve the specific surface area of the positive electrode material so that it absorbs electrolyte. However, the patent does not involve the use of a dispersant for dispersion.
[0005] Patent CN109728258A discloses a dispersion process for lithium iron phosphate positive electrode materials, which is to make a conductive colloid from a conductive agent, fully fuse it, and disperse it four times, including adding a dispersant to change the surface activity of graphene, and using an ultrafine particle crusher to continuously shear with extreme shear force, so that the prepared slurry is evenly dispersed and has good stability. However, this method mainly disperses the slurry by combining conductive micelles with multiple dispersion shearing processes, aiming to improve the degree of dispersion by mechanical dispersion. The process flow is complicated and time-consuming.
[0006] Therefore, in order to solve the problems of serious agglomeration and poor dispersibility of positive electrode slurry particles in the prior art, and easy sedimentation due to increased viscosity as the solid content of the slurry increases, it is urgent to develop a method for preparing a highly dispersible positive electrode slurry for lithium-ion batteries to improve the dispersibility and stability of the slurry, eliminate the appearance of agglomerated particles, improve electrode consistency, reduce battery internal resistance, and enhance the electrochemical performance of the battery. Summary of the invention
[0007] In order to solve the above technical problems existing in the prior art, the present invention provides an in-situ dispersed lithium ion battery positive electrode slurry and a preparation method thereof, which are specifically achieved through the following technical solutions.
[0008] A method for preparing an in-situ dispersed lithium ion battery positive electrode slurry comprises the following steps:
[0009] S1. Glue the binder with NMP solvent to form glue solution after fully dissolving;
[0010] S2, adding the in-situ dispersant raw materials A1 and A2 to the glue solution and stirring at a low speed to dissolve and disperse them, generating anionic compound dispersant A through in-situ substitution reaction, and dispersant A and the glue solution are fully dissolved to form a dispersion stock solution;
[0011] S3, adding dispersant B to the dispersion stock solution formed in S2, and then performing a highly cross-linked hydrothermal reaction in a reactor to obtain a dispersion final solution through the synergistic effect of the two dispersants with different dispersion effects;
[0012] S4. Add a conductive agent and a positive electrode active material to the dispersed final liquid formed in S3 and perform high-speed granulation stirring for 1 to 300 minutes. Finally, adjust the viscosity and solid content to obtain a highly dispersed positive electrode slurry for a lithium-ion battery.
[0013] Furthermore, the components of the positive electrode slurry are active material, conductive agent, binder, and dispersant; calculated by mass fraction: active material 85% to 95%, conductive agent 1% to 12%, binder 1% to 10%, dispersant 0.05% to 5%. The dispersant is the total amount of dispersant A and dispersant B.
[0014] Further, the dispersant A is an in-situ synthesized compound dispersant, the raw material A1 is polyacrylic acid, and the raw material A2 is any one of sodium hydroxide, sodium peroxide, sodium carbonate, and sodium bicarbonate. Dispersant A is a group (-COONa) formed by replacing the carboxyl group (-COOH) of polyacrylic acid with a sodium source.
[0015] Furthermore, the dispersant B is one or more of polyvinyl pyrrolidone, sodium polyacrylate, polyacrylate, and SDS mixed in any proportion.
[0016] Furthermore, the mass ratio of the dispersant A to B is (1-10): (1-10).
[0017] Furthermore, the hydrothermal reaction temperature in step S3 is 80°C to 300°C, and the hydrothermal reaction time is 0.5h to 5h:
[0018] Furthermore, the conductive agent is one or more of SP, rGO, CNTs, VGCF, and carbon nanotube conductive paste mixed in any proportion.
[0019] Furthermore, the positive electrode active material is LiCoO2, LiMn x Fe 1-x PO4, Li[Ni x Co y (Al / Mn) 1-x-y ]One or more of O2 can be mixed in any proportion.
[0020] Furthermore, the viscosity of the lithium-ion battery positive electrode slurry is 2000-20000 mPa·s.
[0021] Furthermore, the solid content of the lithium-ion battery positive electrode slurry is 30-70wt%, and the slurry fineness is 10-45μm.
[0022] The in-situ dispersed lithium ion battery positive electrode slurry is prepared by the method for preparing the in-situ dispersed lithium ion battery positive electrode slurry.
[0023] Compared with the prior art, the technical effects created by the present invention are embodied in:
[0024] (1) The present invention uses polyacrylic acid and a sodium source to dissolve them in the homogenization stage, wherein the carboxyl group (COOH) in the polyacrylic acid reacts with the sodium ion for in-situ synthesis, and the sodium further replaces the hydrogen bond on the carboxyl group to form an anionic compound in the slurry. The energy barrier of the anionic polar head in the slurry is relatively high, and an adsorption effect can be formed to disperse the active substance and inhibit the agglomeration of particles. Therefore, the in-situ substituted anionic compound dispersant has excellent hydrophilicity and high dispersibility. In addition, sodium sources such as sodium hydroxide, sodium peroxide, sodium carbonate, and sodium bicarbonate can also absorb moisture in the slurry or in the subsequent electrode baking process, thereby improving production efficiency and further optimizing the electrochemical performance of the battery.
[0025] (2) The chain-structured dispersant based on polyvinyl pyrrolidone in the present invention is fully dissolved in the glue solution, and forms a steric hindrance effect on the surface of the active material in the slurry in the form of particles, thereby achieving the purpose of dispersing the active material. The anionic and chain-shaped non-ionic dispersants are compounded in the slurry, and the two different dispersion effects formed interact and cooperate with each other, combined with the full dissolution and dispersion of molecular dynamics under high temperature and high pressure during the hydrothermal reaction, thereby achieving an excellent dispersion effect, improving the dispersibility and stability of the slurry, and no agglomerated particles appear, improving the consistency of the pole piece, reducing the internal resistance of the battery, and showing the excellent rate performance and cycle performance of the battery.
[0026] (3) The present invention forms a high adsorption effect on the surface of the dispersion through the in-situ synthesized anionic compound, improves the dispersion effect of the slurry particles, combines the composite synergistic effect of the anionic and chain non-ionic dispersants in the slurry, and forms an adsorption effect that interacts with the steric hindrance effect on the particle surface. Combined with the full dissolution and dispersion of the molecular dynamics of the dispersion liquid under high temperature and high pressure during the hydrothermal reaction, the dispersibility and stability of the slurry are further enhanced, the uniformity inside the electrode sheet is achieved, the conductivity of the electrode sheet is improved, the internal resistance of the battery is reduced, and the excellent rate performance and cycle performance of the battery are achieved, and the discharge capacity of the battery in a low temperature environment is greatly improved. At the same time, the sodium source can also absorb moisture in the slurry or in the subsequent baking process of the electrode sheet, thereby improving production efficiency; the high dispersibility of the slurry also increases the solid content of the slurry, reduces the amount of solvent used in the production process, and greatly reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a comparison chart of the slurry fineness between Comparative Example 1 and Example 1.
[0028] Figure 2 It is a comparison diagram of the normal temperature capacity discharge curves of comparative example 1 and embodiment 1.
[0029] Figure 3 It is a comparison chart of the 3C rate performance discharge curves of comparative example 1 and example 1.
[0030] Figure 4 It is a comparison chart of the normal temperature cycle performance between comparative example 1 and embodiment 1.
[0031] Figure 5 It is a comparison chart of the low temperature performance discharge curves of comparative example 1 and embodiment 1. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further defined below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.
[0033] Example 1
[0034] A method for preparing an in-situ dispersed lithium-ion battery positive electrode slurry is prepared by the following method:
[0035] S1. First, the positive electrode active material, the conductive agent, the binder, and the dispersant are weighed and baked in a mass ratio of 95%:1.5%:3%:0.5%, and the binder is glued with NMP solvent to form a glue solution after being fully dissolved.
[0036] S2, adding in-situ dispersant raw materials A1 and A2 to the glue solution and stirring at a low speed to dissolve and disperse, generating anionic compound dispersant A through in-situ substitution reaction, and dispersant A and the glue solution are fully dissolved to form a dispersion stock solution. The dispersant raw materials A1 are polyacrylic acid, and A2 is sodium hydroxide.
[0037] S3, adding dispersant B to the dispersion stock solution formed in S2 and stirring, then performing a highly cross-linked hydrothermal reaction in a reactor at a certain temperature and time, and obtaining a dispersion final solution through the synergistic effect of the different dispersing effects of the two dispersants. The dispersant B is polyvinyl pyrrolidone. The mass ratio of dispersant A to B is 2.5:7.5 respectively. The hydrothermal reaction temperature is 120°C and the hydrothermal reaction time is 1h.
[0038] S4. Add conductive agent SP and carbon nanotube conductive slurry to the dispersed final liquid formed in S3, and finally add positive electrode active material LiFePO4 for high-speed granulation stirring for 1 to 300 minutes. Finally, adjust the slurry viscosity to 8000mPa·s by adding NMP solvent, the slurry solid content is 54wt%, and the slurry fineness is 20μm, and finally obtain highly dispersed lithium-ion battery positive electrode slurry.
[0039] Example 2
[0040] A method for preparing an in-situ dispersed lithium-ion battery positive electrode slurry is prepared by the following method:
[0041] S1. First, the positive electrode active material, the conductive agent, the binder, and the dispersant are weighed and baked in a mass ratio of 93%:2.9%:4%:0.1%, and the binder is glued with NMP solvent to form a glue solution after being fully dissolved.
[0042] S2, adding in-situ dispersant raw materials A1 and A2 to the glue solution and stirring at a low speed to dissolve and disperse, generating anionic compound dispersant A through in-situ substitution reaction, and dispersant A and the glue solution are fully dissolved to form a dispersion stock solution. The dispersant raw materials A1 are polyacrylic acid, and A2 is sodium carbonate.
[0043] S3, adding dispersant B to the dispersion stock solution formed in S2 and stirring, then performing highly cross-linked hydrothermal reaction in a reactor at a certain temperature and time, and obtaining a dispersion final solution through the synergistic effect of the different dispersing effects of the two dispersants. The dispersant B is polyvinyl pyrrolidone and sodium polyacrylate. The mass ratio of dispersant A to B is 4:6 respectively. The hydrothermal reaction temperature is 300°C and the hydrothermal reaction time is 0.5h.
[0044] S4. Add conductive agent SP, VGCF, and carbon nanotube conductive slurry to the dispersed final liquid formed in S3, and finally add the positive electrode active material LiCoO2 for high-speed granulation stirring. The stirring time is 1 to 300 minutes. Finally, adjust the slurry viscosity to 4000mPa·s by adding NMP solvent, the slurry solid content is 42wt%, and the slurry fineness is 25μm, and finally obtain a highly dispersed lithium-ion battery positive electrode slurry.
[0045] Example 3
[0046] A method for preparing an in-situ dispersed lithium-ion battery positive electrode slurry is prepared by the following method:
[0047] S1. First, the positive electrode active material, the conductive agent, the binder, and the dispersant are weighed and baked in a mass ratio of 90%:3%:6%:1%, and the binder is glued with NMP solvent to form a glue solution after being fully dissolved.
[0048] S2, adding in-situ dispersant raw materials A1 and A2 to the glue solution and stirring at a low speed to dissolve and disperse, generating anionic compound dispersant A through in-situ substitution reaction, and dispersant A and the glue solution are fully dissolved to form a dispersion stock solution. The dispersant raw materials A1 are polyacrylic acid, and A2 is sodium bicarbonate.
[0049] S3, adding dispersant B to the dispersion stock solution formed in S2 and stirring, then performing a highly cross-linked hydrothermal reaction in a reactor at a certain temperature and time, and obtaining a dispersion final solution through the synergistic effect of the different dispersing effects of the two dispersants. The dispersant B is polyvinyl pyrrolidone and SDS. The mass ratio of dispersant A to B is 2:8 respectively. The hydrothermal reaction temperature is 100°C and the hydrothermal reaction time is 3h.
[0050] S4. Add conductive agent SP, rGO, and carbon nanotube conductive slurry to the dispersed final liquid formed in S3, and finally add the positive electrode active material LiFePO4 / LiCoO2 for high-speed granulation stirring. The stirring time is 1 to 300 minutes. Finally, the slurry viscosity is adjusted to 3000mPa·s by adding NMP solvent. The solid content of the slurry is 63wt%, and the slurry fineness is 15μm, and finally a highly dispersed lithium-ion battery positive electrode slurry is obtained.
[0051] Example 4
[0052] A method for preparing an in-situ dispersed lithium-ion battery positive electrode slurry is prepared by the following method:
[0053] S1. First, the positive electrode active material, the conductive agent, the binder, and the dispersant are weighed and baked in a mass ratio of 88%:4.5%:4.5%:3%, and the binder is glued with NMP solvent to form a glue solution after being fully dissolved.
[0054] S2, adding in-situ dispersant raw materials A1 and A2 to the glue solution and stirring at a low speed to dissolve and disperse, generating anionic compound dispersant A through in-situ substitution reaction, and dispersant A and the glue solution are fully dissolved to form a dispersion stock solution. The dispersant raw materials A1 are polyacrylic acid, and A2 is sodium peroxide.
[0055] S3, adding dispersant B to the dispersion stock solution formed in S2 and stirring, then performing a highly cross-linked hydrothermal reaction in a reactor at a certain temperature and time, and obtaining a dispersion final solution through the synergistic effect of the different dispersing effects of the two dispersants. The dispersant B is polyvinyl pyrrolidone and polyacrylate. The mass ratio of dispersant A to B is 3.5:6.5 respectively. The hydrothermal reaction temperature is 200°C and the hydrothermal reaction time is 2h.
[0056] S4, add conductive agent SP, rGO, VGCF to the dispersed final solution formed in S3, and finally add positive electrode active material Li[Ni 0.92 Co 0.05 Mn 0.03 ]O2 is subjected to high-speed granulation stirring for 1 to 300 min, and finally the slurry viscosity is adjusted to 6000 mPa·s by adding NMP solvent, the slurry solid content is 48 wt %, and the slurry fineness is 35 μm, finally obtaining a highly dispersed lithium-ion battery positive electrode slurry.
[0057] Comparative Example 1
[0058] The preparation method of a lithium ion battery positive electrode slurry in Comparative Example 1 is prepared by the following method:
[0059] S1. First, the positive electrode active material, the conductive agent, the binder, and the dispersant are weighed and baked in a mass ratio of 95%:1.5%:3%:0.5%, and the binder is glued with NMP solvent to form a glue solution after being fully dissolved.
[0060] S2. Add conductive agent SP and carbon nanotube conductive slurry to the glue solution, and finally add positive electrode active material LiFePO4 for high-speed granulation stirring for 1 to 300 minutes. Finally, adjust the slurry viscosity to a suitable level by adding NMP solvent, defoam and sieve, and finally obtain a lithium-ion battery positive electrode slurry without in-situ dispersion.
[0061] Comparative experiment:
[0062] The positive electrode slurry of the lithium ion battery prepared in Examples 1 to 4 is coated to form a positive electrode sheet, which is designed and matched with the negative graphite negative electrode sheet. The positive and negative electrode sheets are baked, rolled, and die-cut, and then stacked to form a battery cell. The battery cell is vacuum-baked and packaged with an aluminum-plastic film. Subsequently, the battery cell is injected in a drying room with a humidity of less than 3% RH. After the electrolyte completely infiltrates the battery cell, the battery is sealed. After the aging process and the formation process are completed, vacuum exhaust and secondary sealing are performed to assemble a single battery. The diaphragm used in the battery is a ceramic diaphragm, and the electrolyte is 1 mol / L LiPF6 / EC+EMC+DMC (volume ratio 1:1:1).
[0063] The comparison group of batteries was assembled using the same electrolyte and assembly method as in Application Example 1.
[0064] like Figure 1 As shown, the slurry fineness prepared by Comparative Example 1 and Example 1, which are not dispersed in situ using a dispersant, is different. The slurry fineness prepared in Comparative Example 1 is about 35 μm, indicating that the slurry in Comparative Example 1 has particle agglomeration due to uneven stirring and dispersion, which ultimately leads to the generation of large particles, which may cause the subsequent pole pieces to be unable to stably contact and connect, the conductive network is poor, and the electrochemical performance of the battery is reduced; while the slurry prepared in Example 1 has a fineness of only 15 μm, which is more than twice that of Comparative Example 1, the slurry has a higher consistency and a better coating uniformity, indicating that the slurry dispersed in situ has a higher degree of dispersion, no particle agglomeration, and better slurry stability.
[0065] like Figure 2 As shown, from the comparison of the normal temperature capacity discharge curves of Comparative Example 1 and Example 1, it can be seen that the capacity of Comparative Example 1 discharged at a rate of 1C at room temperature is 2.061Ah, and the discharge capacity of Example 1 is 2.125Ah. The results show that the slurry in Comparative Example 1 is agglomerated, which makes it difficult for a part of the lithium ions to diffuse, and it is difficult to embed into the negative electrode through the electrolyte, so that the charge and discharge process cannot be fully carried out, and therefore the discharge capacity is low. The highly dispersed slurry in Example 1, due to its good uniformity and stability, achieves low internal resistance and high conductivity of the battery electrode, and effectively improves the capacity output capacity of the battery.
[0066] like Figure 3As shown, from the discharge curves of Comparative Example 1 and Example 1 at 3C rate, the discharge capacities of the battery in Comparative Example 1 and Example 1 are 1.835Ah and 2.076Ah, respectively, and the capacity retention rates at 1C discharge are 89.03% and 97.69%, respectively. The discharge platforms of the batteries decrease when the rate is increased from 1C to 3C, wherein the discharge curve of Comparative Example 1 shows a linear downward trend, while Example 1 has a relatively stable long discharge platform, indicating that the highly dispersed slurry dispersed in situ in the present invention still maintains the lowest degree of polarization at high rates, ensures the uniformity and integrity of the electrode, improves the performance defects of the electrode, and realizes the rapid transmission of lithium ion insertion and extraction. This advantage is more obvious when discharging at a large rate, thus showing excellent rate performance.
[0067] like Figure 4 As shown, from the discharge comparison curves of the batteries of Comparative Example 1 and Example 1 subjected to charge and discharge cycles at a 3C rate, it can be seen that the capacity retention rates of the batteries of Comparative Example 1 and Example 1 after 500 cycles are 84.3% and 94.1%, respectively. The results show that the slurry in Example 1 has a significant slurry dispersion effect through the highly synergistic effect of adsorption effect and steric hindrance effect, effectively suppresses the agglomeration defects of the particles in the pole piece, prevents the degradation of the electrode structure, reduces the interface impedance and the internal polarization of the battery, reduces the capacity loss of the battery during a long cycle, and improves the cycle capacity retention rate by nearly 10%.
[0068] from Figure 5 It can be seen that the discharge capacity of the battery in Comparative Example 1 at a low temperature of -20°C and 1C discharge to 1.5V is 1.353Ah, and the low-temperature discharge capacity retention rate relative to 1C at room temperature is 65.65%, while the discharge capacity of the battery in Example 1 is 1.702Ah, and the low-temperature discharge capacity retention rate relative to 1C at room temperature is 80.09%. The low-temperature capacity output is greatly improved, indicating that the in-situ dispersed slurry preparation method in the present invention effectively increases the capacity output capacity of the battery at low temperatures. In addition, at the initial stage of low-temperature discharge, the polarization voltage of Comparative Example 1 is 2.75V, while the voltage of Example 1 is increased to more than 3.1V, indicating that the highly dispersed slurry in the present invention also reduces the polarization degree of the battery during low-temperature discharge, thereby achieving excellent low-temperature discharge characteristics of the battery.
[0069] Table 1 below shows the discharge performance data of the batteries in various embodiments:
[0070] Table 1 Performance data of various embodiments and comparative examples
[0071]
[0072] It can be seen from the data in Table 1 above that the in-situ dispersed lithium-ion battery positive electrode slurry provided by the present invention improves the dispersion degree and stability of the slurry through the composite synergistic effect of the adsorption effect and the steric hindrance effect constructed by in-situ dispersion, reduces the adverse effects of particle agglomeration in the electrode sheet, and improves the infiltration degree of the electrolyte in the electrode sheet, thereby realizing the high mass transfer and charge transfer dynamics of lithium ion transmission during the charge and discharge process of the battery, greatly improving the battery's high-rate capacity output capability and low-temperature discharge characteristics, and effectively improving the battery's cycle performance.
[0073] Finally, it should be pointed out that the above embodiments are only representative examples of the present invention. Obviously, the technical solution of the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by ordinary technicians in this field should be considered as the protection scope of the present invention.
Claims
1. A method for preparing an in-situ dispersed lithium ion battery positive electrode slurry, characterized in that: The following steps are involved: S1, glue the binder with NMP solvent to form glue solution after fully dissolving; S2, adding the in-situ dispersant raw materials A1 and A2 to the glue solution and stirring at a low speed to dissolve and disperse them, generating anionic compound dispersant A through in-situ substitution reaction, and dispersant A and the glue solution are fully dissolved to form a dispersion stock solution; S3, adding dispersant B to the dispersion stock solution formed in S2, and then performing a highly cross-linked hydrothermal reaction in a reactor to obtain a dispersion final solution through the synergistic effect of the two dispersants with different dispersion effects; S4. Add a conductive agent and a positive electrode active material to the dispersed final liquid formed in S3 and perform high-speed granulation stirring for 1 to 300 minutes. Finally, adjust the viscosity and solid content to obtain a highly dispersed positive electrode slurry for a lithium-ion battery.
2. The method for preparing an in-situ dispersed lithium ion battery positive electrode slurry according to claim 1, characterized in that: The components of the positive electrode slurry are active material, conductive agent, binder and dispersant; calculated by mass fraction: active material 85% to 95%, conductive agent 1% to 12%, binder 1% to 10%, dispersant 0.05% to 5%.
3. The method for preparing an in-situ dispersed lithium ion battery positive electrode slurry according to claim 1, characterized in that: The dispersant A is an in-situ synthesized compound dispersant, the raw material A1 is polyacrylic acid, and the raw material A2 is any one of sodium hydroxide, sodium peroxide, sodium carbonate, and sodium bicarbonate.
4. The method for preparing an in-situ dispersed lithium ion battery positive electrode slurry according to claim 1, characterized in that: The dispersant B is one or more of polyvinyl pyrrolidone, sodium polyacrylate, polyacrylate, and SDS mixed in any proportion.
5. The method for preparing an in-situ dispersed lithium ion battery positive electrode slurry according to claim 1, characterized in that: The mass ratio of the dispersant A to B is (1-10): (1-10).
6. The method for preparing an in-situ dispersed lithium ion battery positive electrode slurry according to claim 1, characterized in that: The hydrothermal reaction temperature in step S3 is 80° C. to 300° C., and the hydrothermal reaction time is 0.5 h to 5 h.
7. The method for preparing an in-situ dispersed lithium ion battery positive electrode slurry according to claim 1, characterized in that: The conductive agent is one or more of SP, rGO, CNTs, VGCF, and carbon nanotube conductive paste mixed in any proportion.
8. The method for preparing an in-situ dispersed lithium ion battery positive electrode slurry according to claim 1, characterized in that: The positive electrode active material is LiCoO2, LiMn x Fe 1-x PO4, Li[Ni x Co y (Al / Mn) 1-x-y ]One or more of O2 can be mixed in any proportion.
9. The method for preparing an in-situ dispersed lithium ion battery positive electrode slurry according to claim 1, characterized in that: The lithium ion battery positive electrode slurry has a viscosity of 2000 to 20000 mPa·s, a solid content of 30 to 70 wt%, and a slurry fineness of 10 to 45 μm. 10 . The in-situ dispersed lithium ion battery positive electrode slurry prepared by the method for preparing the in-situ dispersed lithium ion battery positive electrode slurry according to claim 1 .
Citation Information
Patent Citations
Dispersion process of lithium iron phosphate cathode material
CN109728258A
Preparation method of high-rate lithium ion battery cathode slurry
CN111162262A
Cited By
Method for improving stability of sodium ion battery polyanion positive electrode slurry
CN120600810A
Preparation method and application of high-viscosity slurry homogeneous structure pole piece
CN121617910A